2020
DOI: 10.1136/oemed-2020-106418
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) colonisation and infection among livestock workers and veterinarians: a systematic review and meta-analysis

Abstract: ObjectivesMethicillin-resistant Staphylococcus aureus (MRSA) is an increasing public health concern worldwide. The objective of this study was to calculate a summary odds ratio (OR) of livestock-associated MRSA colonisation and infection in humans, and to determine specific risk factors in livestock production contributing to MRSA colonisation.MethodsWe screened PubMed and Embase for studies published from 2005 to 2019 inclusive, reporting livestock-associated (LA)-MRSA colonisation and infection among livesto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 59 publications
2
45
0
Order By: Relevance
“…During the last decade, livestock have been considered to be a great reservoir of MRSA with high potential of zoonotic transmission to humans [ 3 ]. It has been observed that the spread of LA-MRSA from animals to humans occurs frequently and that livestock workers present a high risk for LA-MRSA colonisation and subsequent infection [ 4 ]. The abusive use of antimicrobials like tetracycline in food production animals leads to the selective pressure of tetracycline-resistant (Tet R ) LA-MRSA isolates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, livestock have been considered to be a great reservoir of MRSA with high potential of zoonotic transmission to humans [ 3 ]. It has been observed that the spread of LA-MRSA from animals to humans occurs frequently and that livestock workers present a high risk for LA-MRSA colonisation and subsequent infection [ 4 ]. The abusive use of antimicrobials like tetracycline in food production animals leads to the selective pressure of tetracycline-resistant (Tet R ) LA-MRSA isolates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…S. argenteus with different antibiotic resistance genes have been reported ( Aung et al., 2021 ; Eshaghi et al., 2021 ), including an isolate with elevated MIC (4µg/ml) to daptomycin and vancomycin in the United States ( Hao et al., 2020 ). Recent studies from China ( Chen and Wu, 2020 ) and Japan ( Wakabayashi et al., 2021 ) have also identified S. argenteus from retail foods and an emerging bovine mastitis pathogen in Thailand ( Pumipuntu, 2019 ). We could not ascertain if the study individual received mupirocin or not.…”
Section: Resultsmentioning
confidence: 99%
“…As a final element to this study, the utility of the selected AVNP was assessed further by evaluating their activity against the bacterium S. aureus . Methicillin-resistant S. aureus (MRSA) occurs widely in pig populations globally, and while colonization alone does not cause disease in pigs, it is of great public health importance [ 35 , 36 ]. AVNP2, CuNP, and CuONP all showed bactericidal activity against the three S. aureus strains tested, whilst WCNP showed no bactericidal effect at any of the concentrations tested.…”
Section: Resultsmentioning
confidence: 99%